Modeling and Performance of Microwave and Millimeter-Wave Layered Waveguide Filters - Ardavan Rahimian (Institute of Advanced Engineering and Science, 2013)
This paper presents the novel designs, analysis, and performance of 4-pole and 8-pole microwave and millimeter-wave (MMW) waveguide filters for operation at X and Y frequency bands. The waveguide filters have been designed and analyzed based on the mode matching and coupled resonators design techniques employing layered technology. Thorough waveguide filters working at X-band and Y-band have been designed, analyzed, fabricated, and tested along with the analysis of the output characteristics. Accurate designs of RF waveguides along with their filters based on the E-plane filter concept have been carried out with the ability of fitting into layered technology in high frequency production techniques. The filters demonstrate the appropriateness in order to develop high-performance well-established designs for systems that are intended for the multi-layer microwave, millimeter- and sub-millimeter-waves devices and systems; with the potential employment in radar, satellite, and radio astronomy applications.DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2411